Making mothers: parenting classes in a women's jail. Issue 4 (1st October 2016) - Aiello, Brittnie
Abstract: In the wake of the War on Drugs, more mothers are incarcerated in US prisons and jails than ever before. Parenting classes have become ubiquitous in penal facilities that incarcerate women, but research about mothers' experience in parenting class is limited to measures of efficacy about things like parenting attitudes and mental-health indicators. This study supplements existing research by adding an ethnographic lens to women's experiences with parenting classes during incarceration. Drawing on 18 months of participant observation in the women's unit of a county jail and 83 interviews with incarcerated mothers, I analyze incarcerated mothers' experiences with parenting classes. Staff and inmates used parenting classes to create ways for women to do mothering during incarceration. Mothering in your head, longing to mother, and guilt as mothering enabled incarcerated mothers to maintain their identities as mothers despite their separation from their children. However, these practices could also be poor substitutes for spending time with children and did not necessarily reflect the reality of women's lives outside of jail. These ways of doing mothering from afar were also a form of social control for the penal institution, as these mothering behaviors were consistent with being a good inmate.